An investigation into the effectiveness of an anti-bullying campaign - Herrick, Caroline (2012)
There is a body of research that emphasises the role that peers can have in either fuelling or preventing bullying behaviour. Bystanders typically reinforce bullying by joining in or passively watching (O'Connell, Pepler and Craig 1999). Social identity theory (Tajfel and Turner 1979) states that within a social group individuals are motivated to maintain a positive social identity and do so by adhering to group norms. Therefore, if bullying is normative within a group pupils are more likely to join in or passively watch (Duffy and Nesdale 2008; Gini 2006). This study evaluates the effectiveness of 'Defeat Bullying' (NSPCC 2007), a five week whole class anti-bullying curriculum. The overall aim of the curriculum was to create an anti-bullying group norm within the class. A pre-test, post-test non-equivalent groups quasi experimental design was employed, with an eight week follow up. Pupils aged 9-10 (year 5) from three schools in a predominately rural Local Authority (LA) in Yorkshire participated in the study (n = 69). School 1 received the intervention, School 2 received the intervention plus parental involvement and School 3 was the control group. Pupils' reported levels of bullying, attitudes towards bullying and knowledge of how to intervene in bullying situations were measured. Questionnaires regarding the pupils' difficult and prosocial behaviour were completed by the teachers. The impact of parental involvement on the effectiveness of the intervention was also explored. 'Defeat Bullying' (NSPCC 2007) did not have a statistically significant effect on any of the factors measured, which suggests there was no overall effect on the group norms regarding bullying. Furthermore, there was no statistically significant difference between School 1 and School 2 who received the intervention plus parental involvement. Possible reasons for the non significant results and the implications of this are discussed. The likelihood of changing group norms through the delivery of an anti-bullying curriculum is considered. The study raises questions in terms of whether or not parental involvement is important in anti-bullying interventions and if so what type of parental involvement is the most effective.